Analysis of the Elastic Large Deflection Behavior for Metal Plates under Nonuniformly Distributed Lateral Pressure with In-Plane Loads - Paik, Jeom Kee; Kim, Bong Ju; Park, Ju Hye (Journal of Applied Mathematics, 2012)
The Galerkin method is applied to analyze the elastic large deflection behavior of metal plates subject to a combination of in-plane loads such as biaxial loads, edge shear and biaxial inplane bending moments, and uniformly or nonuniformly distributed lateral pressure loads. The motive of the present study was initiated by the fact that metal plates of ships and ship-shaped offshore structures at sea are often subjected to non-uniformly distributed lateral pressure loads arising from cargo or water pressure, together with inplane axial loads or inplane bending moments, but the current practice of the maritime industry usually applies some simplified design methods assuming that the non-uniform pressure distribution in the plates can be replaced by an equivalence of uniform pressure distribution. Applied examples are presented, demonstrating that the current plate design methods of the maritime industry may be inappropriate when the non-uniformity of lateral pressure loads becomes more significant.